2021
DOI: 10.3390/agronomy11112163
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Release in Soils Amended with Different Organic and Inorganic Fertilizers under Contrasting Moisture Regimes: A Laboratory Incubation Study

Abstract: Understanding nitrogen (N) release patterns and kinetics is a key challenge for improving N use efficiency in any agroecosystem. An incubation experiment was done to study the N release pattern and kinetics of contrasting soils amended with compost (CO), poultry manure (PM), rice husk biochar (RHB), poultry manure biochar (PMB) and cowdung (CD) combined with chemical fertilizer (integrated plant nutrient system, IPNS approach) under two moisture regimes, viz. field capacity (FC) and continuous standing water (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Clay content increases with the reduction of sand content. Medeiros et al (2018) report that electrical conductivity (EC) demonstrates a positive correlation with soil water content, while Uddin et al (2021) found that total N increases alongside rising water content. High clay content is well known to cause and influences root growth patterns (Bonomelli et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Clay content increases with the reduction of sand content. Medeiros et al (2018) report that electrical conductivity (EC) demonstrates a positive correlation with soil water content, while Uddin et al (2021) found that total N increases alongside rising water content. High clay content is well known to cause and influences root growth patterns (Bonomelli et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The surface soil (0–15 cm) samples (50 g) from each treatment were incubated in a BOD incubator (model SA‐403 AARK international, India) at room temperature (25 ± 2°C) with moisture level at field capacity. The field capacity was maintained at 25% with respect to the sandy loam texture of the experimental soil (Uddin et al, 2021; Yu et al, 2023). The DTPA‐extractable Fe was estimated from each sample at 1, 5, 10, 20, 30, 40, 50 and 60 days of incubation without any extraneous addition of Fe.…”
Section: Methodsmentioning
confidence: 99%
“…However, for pragmatic reasons, observational study periods usually cover only a few years under a narrow range of conditions and are often not continuous over that time [38]. In parallel, researchers use incubation experiments to gain a deeper understanding of nitrogen dynamics [39]. During these experiments, soil samples are analyzed under controlled conditions to assess the impact of factors such as soil moisture, texture, temperature, and various fertilization treatments on gas emissions [40].…”
Section: Introductionmentioning
confidence: 99%